2000
DOI: 10.1111/j.1469-7793.2000.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive neuroendocrine negative feedback control of neurogenic inflammation activated by capsaicin in the rat paw: role of the adrenal medulla

Abstract: Bradykinin (BK)-induced synovial plasma extravasation (PE) in the rat knee joint is a neurogenic inflammatory response which is dependent on the sympathetic innervation of the synovia, but not on impulse activity in the sympathetic neurones (Miao et al. 1996a,b). Recently we have shown in the rat that this neurogenic inflammation is depressed in a frequency-dependent manner during activation of afferent C-fibres generated by electrical stimulation of the contralateral hindpaw at û 1-3 Hz. Hypophysectomy, blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 26 publications
2
19
0
1
Order By: Relevance
“…This unexpected reduction of microglial activity may be explained by vagal inhibition of spinal sensory signaling. It has been previously demonstrated that vagal activity influences a pathway of descending inhibition from the hindbrain—presumably the NTS—to the spinal afferent terminals in the dorsal horns of the SC [30;31]. The subdiaphragmatic vagotomy performed in our study would disrupt the same descending pathway.…”
Section: Discussionsupporting
confidence: 52%
“…This unexpected reduction of microglial activity may be explained by vagal inhibition of spinal sensory signaling. It has been previously demonstrated that vagal activity influences a pathway of descending inhibition from the hindbrain—presumably the NTS—to the spinal afferent terminals in the dorsal horns of the SC [30;31]. The subdiaphragmatic vagotomy performed in our study would disrupt the same descending pathway.…”
Section: Discussionsupporting
confidence: 52%
“…Vagal activation leads to visceral pain, for example, angina pectoris (Rosen, 2012) and pancreatic pain (Schwartz et al, 2011). However, vagal activation can also reduce somatic pain via central pathways (J€ anig, 2005;Miao et al, 2000), and a nerve tracing study suggested that vagal afferent may contribute to chronic discogenic neck pain (Fujimoto et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Published data have shown that signals transmitted by afferent pathways of the vagus nerve are involved in modulating of HPA axis activity (Miao et al, 2000;O'Keane et al, 2005). For example, vagotomy prevents activation of HPA axis by immune stimuli (Goehler et al, 2005;Watkins et al, 1995).…”
Section: Discussionmentioning
confidence: 99%